A 450 mV Tunable Low-Frequency OTA-C Third-Order Elliptic Low-Pass Filter for Bio-Signal Applications - Kumngern, Montree; Kulej, Tomasz; Khateb, Fabian (My University, 2025)
This paper introduces a tunable third-order elliptic low-pass OTA-C filter specifically designed for biological signal applications. The proposed filter leverages a multiple-input operational transconductance amplifier (MI-OTA) that operates at low voltage and low power consumption. This innovative approach simplifies the filter topology and significantly reduces the number of active and passive components required. By utilizing the multiple-input capability of the OTA, the voltage gains of the low-pass transfer function can be easily increased. The filter operates with a supply voltage of 450 mV and consumes only 40.5 nW of power while achieving a cutoff frequency of 112.9 Hz and a dynamic range (DR) of 66.7 dB at 1% total harmonic distortion (THD). The filter’s performance was validated through the effective filtering of interfering ECG signals. The design and simulations were carried out using the Cadence environment and TSMC’s 0.18~\mu m CMOS technology. Monte Carlo (MC) analysis and process, voltage, and temperature (PVT) corner analysis were conducted to ensure the robustness of the design.
Keywords: Active filter; biomedical system; low-voltage low-power circuit; operational transconductance amplifier